الشيخ أحمد بن إسماعيل الگوراني سيرته وجهوده العلمية - علي, عادل محمد; فرج, شكار عثمان حمه‌ (Sulaimani Journal for Humanities, 2022)
The Kurdish scientist “Ahmed, son of Ismail Gorani”, also known as “Mala Gorani”; was one of the famous and competent scientists of Kurds, who belonged to “Goran” clan and lived in 9th Hijri (AH) Century. This scientist was born in 813 AH in “Jalawla “town in “Garmian” Administration/District. His educational beginning was not mentioned in any source, but in the beginning of his youth, he left Southern Kurdistan to Northern Kurdistan so as to study science more (to learn more knowledge). There, he studied Arabic language, tafseer, fiqh, and qira’aat (Qur’an recitations); and then he moved to Sham Country, where he got much more talented by learning from some other scientists. After that he left to Egypt, where he learned Hadith Science and some other sciences from a few famous scientists. “Mala Gorani” was given some political positions due to his talents, intelligence, and being multi-lingual, at the same time he was teaching fiqh lessons at some schools in Cairo. He continued like that until a problem happened between him and a Hanafi Kadhi (Judge), as finally “Mala Gorani” was expelled from Egypt and moved to Sham another time. Then, he left to the Rome territories, where politicians found out Gorani’s talents and intelligence in sciences, and gave him some important duties accordingly, such as formal judgement and fatwas. He stayed in Rome until his death. “Gorani” has left almost fifteen books, in which tens of master and doctorate degrees have been written. Most of them are about qira’aat (Qur’an recitation), and some of them are more than hundreds of papers, and many of them have been published. After eight years of bravery and teaching sciences, “Mala Gorani” died in 893 AH in the city of Istanbul and was buried there.